The development of a Utopian city? Comparing land-and skyscapes in Santa Cruz de Tenerife and San Cristobal de la Laguna - Gangui, Alejandro (2018)
We discuss the peculiar planning of the city of San Cristóbal de La Laguna, in the Canary Island of Tenerife (Spain), when compared to the nearby and essentially contemporary Santa Cruz de Tenerife, which served as a maritime port of the former city. For this we review our previous study of the exact spatial orientation of twenty-one historic Christian churches currently existing in the old part of La Laguna, which we compare with the analysis of six similar buildings located in Santa Cruz, and presented here for the first time. In both cities, we take the spatial orientation of historic churches as good indicators of the original layout of the respective urban lattices. Although we find a clear orientation pattern for La Laguna, which singles out an absolute-value astronomical declination slightly below 20°, pointing to a preferred date close to the July 25th feast-day of San Cristóbal de Licia, in the case of Santa Cruz this trend is not followed. On the contrary, the pattern we find for Santa Cruz, within the uncertainties due to the low statistics, and apart from one equinoctial and one solstitial oriented churches, is consistent with an orographic orientation within the canonic limits of sunrise. This result highlights the uniqueness of the city of La Laguna, and supports the idea suggesting its deliberate planning in the early 16th century.